Survival and predictors of mortality among HIV-positive children on antiretroviral therapy in public hospitals - Yalemgeta Biyazin; Kalkidan Wondwossen; Azene Bantie Wubie; Melese Getachew; Bereket Gebremichael (Taylor & Francis Group, 2022)
Background Human immunodeficiency virus and acquired immunodeficiency syndrome had created enormous challenges worldwide, and continues to be the world's serious health and development challenges. Globally, at the end 2017, there were 1.8 million children (< 15 years) living with HIV. The survival of HIV-positive children treated with ART depends on a variety of factors, which might vary greatly with economic, socio-demographic, behavioral risk, and health factors. This study aimed to assess survival status and predictors of mortality among HIV-positive children on antiretroviral therapy at East Gojjam Zone Public hospitals, Northwest Ethiopia. Methods An institution-based retrospective cohort study was conducted in selected hospitals of the East Gojjam zone, Northwest Ethiopia, among < 15-year-old children who were newly enrolled in HIV care clinic from January 1st, 2014 to December 31, 2018. Data were collected from patient charts from March 1 to 22, 2019 using a standardized checklist. Data were analyzed by SPSS version 24. A Kaplan-Meier curve and log-rank test were used to estimate the survival time and compare survival curves between variables. Multivariable Cox proportional-hazards model was fitted to identify predictors of survival status taking p-value < 0.05 as statistically significant. Result In this study, a total of 251 HIV-positive children on ART were followed up for a total of 60 months, with a mean survival time of 55.54 (± 0.83) (95% CI: 53.90-57.17) months. The overall mortality incidence rate in the cohort during the 626 Child-Year-Observation (CYO) was 2.56/100 CYO. The overall estimated survival probability after starting ART was 0.90 at 60 months of follow-up. In this study age < 5 years, Hgb < 10 gm/dl, CD4 count below threshold, cotrimoxazole preventive therapy, and subnormal weight for height were statistically significant predictors of survival status (P < 0.05). Conclusion and recommendation Age, hemoglobin level, CD4 count, weight for height, and not taking cotrimoxazole preventive therapy were independent predictors of mortality. Therefore, concerned stakeholders should focus on the above-mentioned predictors of mortality and nutritional interventions to enhance the survival of HIV-infected children on antiretroviral therapy.